PENGEMBANGAN PRIORITAS PEMBANGUNAN KORIDOR KEMILING-TANGGAMUS PROVINSI LAMPUNG - Michael; Reza Asriandi Eka Putra; Siti Rahma (Jurnal Infrastruktur, 2021)
The Sumatera West-Intercity Road has had an essential role in connecting several regions in Sumatera Province because it has been the main route for logistic and passenger movements, especially in the Sumatera Island region. Besides, this road network also has a vital role in supporting economic growth, industry, and tourism for the surrounding area. This corridor already developed then continues to grow with traffic congestion appears at several locations such as Gedong Tataan District, Gisting District, and Pringsewu District. In this study, a feasibility study evaluates four road network improvement options. The first alternative is the widening of the Kemiling Sub-District Section, Bandar Lampung to Kota Agung District, Tanggamus Regency. The Second is a construction of four ring- roads, Gedong Tataan Ring-Road, Pringsewu Ring-Road, Talang Padang Ring-Road, and Gisting Ring-Road. The third alternative is planning the construction of a new corridor from Bandar Lampung to Pringsewu, and the last alternative is a construction of all new corridor from Bandar Lampung to Tanggamus. The evaluation carries by a multi-criteria analysis by considering six aspects of evaluation, including economic feasibility, level of road functionality, social and environmental impacts, development of the road network, vehicle movement, and accessibility of funding. From the results of the study, the main priority is the development of alternative 2 (Development four ring-road) with point 76.